2007
DOI: 10.1021/cm062595o
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Nonlinear Nanopores in Alumina Films

Abstract: Controlled and convenient synthetic approaches for more complex-shaped nanotubes and nanowires of different materials are needed to further advance the field of nanoscience and nanotechnology. In this paper, we report the synthesis and characterization of nonlinear nanopores (such as curved and dendritic nanopores) containing alumina films. We show that control over the orientation of nanopores can be accomplished by controlling the geometric shape of aluminum substrates on which nanoporous alumina is grown. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
(36 reference statements)
0
26
0
Order By: Relevance
“…This phenomenon can be ascribed to the competitive growth of nanopores based on the pre-patterned aluminum substrate with submicron cambered surfaces. 62,63 At the initial stage of anodization, the growth directions of the nanopores are not parallel to each other, but perpendicular to the cambered surfaces with radial directions. As a result, the competitive growth of the nanopores cannot only occur in each submicron cambered surface, but also occur between these surfaces (Figure 6), which will decrease the longitudinal film growth rate to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can be ascribed to the competitive growth of nanopores based on the pre-patterned aluminum substrate with submicron cambered surfaces. 62,63 At the initial stage of anodization, the growth directions of the nanopores are not parallel to each other, but perpendicular to the cambered surfaces with radial directions. As a result, the competitive growth of the nanopores cannot only occur in each submicron cambered surface, but also occur between these surfaces (Figure 6), which will decrease the longitudinal film growth rate to a certain extent.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the competitive growth of the nanopores cannot only occur in each submicron cambered surface, but also occur between these surfaces (Figure 6), which will decrease the longitudinal film growth rate to a certain extent. 49,[62][63][64][65] As the anodization proceeds, the degree of competitive growth will be decreased because of the self-organized regime originated from the compression stress in the AAO film, 50,66 and the nanopores gradually tend to grow parallel with each other, thus obtaining a faster longitudinal film growth rate.…”
Section: Resultsmentioning
confidence: 99%
“…As most of the studies have been focused on synthesizing linear nanopores in alumina film [54], nonlinear nanopores in alumina films were fabricated and studied by Kohli' s group [55]. They reported that the shape and the orientation of the nanotubes in the AAO film highly depended on the geometric …”
Section: Synthesis Of Nano-porous Materials With Hierarchical Poresmentioning
confidence: 99%
“…As such, pertinent issues are also discussed with reference to the anodic porous alumina in this section. Anodic growth of nanoporous alumina on curved surface has been studied in a few reports, [69][70][71][72] which can be used to mirror the growth of titania nanotubes on similar substrates. Major features of the nanopores grown on concave and convex surfaces are summarized in Firstly, all of the nanopores initiate perpendicularly to the local surface (or tangent line to the surface), regardless of the geometric shape of the substrate.…”
Section: Conformal Growth On Curved or Patterned Surfacesmentioning
confidence: 99%